2007
DOI: 10.1016/j.neuroscience.2007.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Fewer driver synapses in higher order than in first order thalamic relays

Abstract: Abstract-We used electron microscopy to determine the relative numbers of the three synaptic terminal types, RL (round vesicle, large terminal), RS (round vesicles, small terminal), and F (flattened vesicles), found in several representative thalamic nuclei in cats chosen as representative examples of first and higher order thalamic nuclei, where the first order nuclei relay subcortical information mainly to primary sensory cortex, and the higher order nuclei largely relay information from one cortical area to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
1
20
2
Order By: Relevance
“…Because the thalamic reticular nucleus is involved in the corticothalamic feedback, our data would also suggest information processing in the higher-order relays is under more extensive (disynaptic, inhibitory) control from the cortex. This notion is consistent with recent evidence that higher-order thalamic relays generally have a greater preponderance of modulatory inputs (Van Horn and Sherman 2007;Wang et al 2002) and are relatively selectively innervated by GABAergic inputs from the zona incerta and anterior pretectal nucleus (Bartho et al 2007;Bokor et al 2005;Trageser and Keller 2004) and by dopaminergic inputs (Sanchez-Gonzalez et al 2005).…”
Section: Functional Significancesupporting
confidence: 91%
“…Because the thalamic reticular nucleus is involved in the corticothalamic feedback, our data would also suggest information processing in the higher-order relays is under more extensive (disynaptic, inhibitory) control from the cortex. This notion is consistent with recent evidence that higher-order thalamic relays generally have a greater preponderance of modulatory inputs (Van Horn and Sherman 2007;Wang et al 2002) and are relatively selectively innervated by GABAergic inputs from the zona incerta and anterior pretectal nucleus (Bartho et al 2007;Bokor et al 2005;Trageser and Keller 2004) and by dopaminergic inputs (Sanchez-Gonzalez et al 2005).…”
Section: Functional Significancesupporting
confidence: 91%
“…Earlier studies for the cat and rat showed that the ratio of drivers (RL) to modulators (RS and F) is higher in the first than the higher-order thalamic relays [9][10][11][12]. Most strikingly, the present study of GAERS shows an abnormality of this relationship.…”
Section: Discussioncontrasting
confidence: 54%
“…Earlier studies on the thalamus of normal rats and cats have shown that the ratios of different terminal types vary between thalamic nuclei [9][10][11][12]. Three major terminal types, RL (round vesicles and large terminals), RS (round vesicles and small terminals) and F (flattened vesicles) terminals, have been described in the thalamus [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…r The relative percentage of driver versus other synapses is significantly lower in higher order relays at roughly 2% versus 5% (168,169,180), suggesting that there is relatively more modulation of higher order relay cells.…”
Section: First and Higher Order Relaysmentioning
confidence: 99%